Determinants of integrated teaching capacity among teachers in ethnic minority primary schools in northern Vietnam - Thi Thu, Hang Nguyen; Nguyen, Chuyen T. H. (Institute of Advanced Engineering and Science, 2025)
This study explores factors affecting the integrated teaching capacity of primary school teachers in ethnic minority schools in the Northern mountainous regions of Vietnam. Given the challenges of linguistic and cultural diversity in this context, the research aims to address gaps in current practices and propose measures for improvement. A quantitative approach was adopted, surveying 280 teachers and administrators using exploratory factor analysis (EFA) and multivariate regression. The results identify four primary factors influencing teaching capacity: i) language, culture, and parent coordination; ii) teacher capacity and community participation; iii) teaching materials, equipment, and teacher attitudes; and iv) policies and support from management agencies. Among these, language, culture, and parent coordination are the most impactful. The study underscores the need for targeted teacher training programs and improved collaboration with local communities to enhance teaching outcomes. These findings provide actionable insights for policymakers and educators to improve integrated teaching in ethnically diverse and economically challenged regions.